INOVASI PEMBELAJARAN SASTRA PADA MATA PELAJARAN BAHASA JERMAN DI SMA - Ryan Nuansa Dirga (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This paper describes innovation of lietarure teaching in Germanic for SMA students.   Curriculum change has an immense effort for teachers to promote adaptation on their teaching.  In the 2013 Curriculum for SMA, in this context of analysis, innovation for teaching materials and teaching methods used are required as the inquiry based teaching is prominent in this context. The problems of curriculum innovation requires teachers creativity in terms of instructional designs, including: syllabus, lesson plan, teaching materials, methos of teaching and assessment.  This paper argues that innovation in teaching Germany for SMA students should start from the instructional design that puts emphases on teaching materials and teaching methods using for exapmle: project-based teaching, inquiry-based teaching.